Phytochemical, metabolic profiling and antiparasitic potential from Inga semialata leaves (Fabaceae) - Lima, Nerilson M. [UNESP]; de Marqui, Sara R. [UNESP]; Andrade, Teresinha de Jesus A. S.; Silva, Dulce H. S. [UNESP] (Taylor & Francis, 2020)
Natural Products phytochemical provide a rich source for therapeutic discovery and has led to the development of many drugs. Thus, the aim of this study was to obtaining a metabolic profiling from ethanol extract of Inga semialata leaves (EEIS) selected by bioassay antimalarial and nematostatic and identify metabolites in mixture by co-injection experiments and NMR spectroscopy. The chemical composition of this species indicated a wide variety of aromatic acids (vanillic acid, 3,4,5-trimethoxy benzoic acid, gallic acid, methyl gallate, p-coumaric acid and ferulic acid), flavonoids (quercetin, myricetin-3-O-rhamnoside and myricetin-3-O-(2-O-galloyl)-α-rhamnopyranoside), triterpenes (lupeol, α-amyrin, friedelin and oleanolic acid) and the 2-hydroxyethyl-dodecanoate. The antimalarial assay showed that the I. semialatan-hexane fraction presented higher inhibition percentage than the Chloroquine standard and may be considered a potential source of compounds with antimalarial activity while the EEIS and its fractions showed nematostatic potential below 17% in the assay of nematostatic evaluation against the parasite Meloidogyne incognita.
Keywords: antimalarial; aromatic acids; flavonoids; Inga semialata; nematostatic; triterpenes